Analysis of Recruitment, Talent Management, and Work Engagement Impact on Sustainability Organization at International Freight Forwarding Company - Jumawan; Wastam Wahyu Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to look at the relationship between variables and analyze the factors causing decreased organizational sustainability. This research uses a literature review study to systematically review previous articles to see their correlation with current research. The results show a relationship between all independent variables and the dependent variable. This finding could really be something new in qualitative research, organizational sustainability can increase with effective recruitment, and the implementation of talent management at all levels, thus creating an atmosphere of work engagement from new employees entering work until retirement in expedition companies. In human resource management research, there is no research framework like this article and the hypotheses in this research are very rarely found in previous research.